2009 Atlanta Conference on Science and Innovation Policy 2009
DOI: 10.1109/acsip.2009.5367856
|View full text |Cite
|
Sign up to set email alerts
|

International co-authorship and research team performance in Colombia

Abstract: This article examines the ways in which International Scientific Collaboration, as observed by the co-authorship of journal articles written by local scientists and partners located overseas, affects the ability of research teams to produce bibliographic outputs and to contribute to local knowledge. A sample of 672 teams was randomly selected for the analyses. In addition, 20 interviews with experts and team members were administered to discuss models and results. Results show that co-authoring with partners l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Such collaborations can be in the forms of exchanging ideas, conducting experiments, or participating in the same research program. Past studies using coauthorship as the measurement of research collaboration indicated that there are extensive research collaborations among authors from different departments, institutions, and countries and consistently confirmed the increasing trend of research collaboration (Adams, Black, Clemmons, & Stephan, ; Gazni, Sugimoto, & Didegah, ; Glänzel & Schubert, ; Narin, Stevens, & Whitlow, ; Ordonez‐Matamoros, Cozzens, & Garcia, ; van Raan, ). Even though the phenomenon of research collaboration has become more conspicuous, possible driving forces and impacts of this phenomenon continue to call for further investigations.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Such collaborations can be in the forms of exchanging ideas, conducting experiments, or participating in the same research program. Past studies using coauthorship as the measurement of research collaboration indicated that there are extensive research collaborations among authors from different departments, institutions, and countries and consistently confirmed the increasing trend of research collaboration (Adams, Black, Clemmons, & Stephan, ; Gazni, Sugimoto, & Didegah, ; Glänzel & Schubert, ; Narin, Stevens, & Whitlow, ; Ordonez‐Matamoros, Cozzens, & Garcia, ; van Raan, ). Even though the phenomenon of research collaboration has become more conspicuous, possible driving forces and impacts of this phenomenon continue to call for further investigations.…”
Section: Introductionmentioning
confidence: 71%
“…Research collaboration is often measured by coauthorship of publications (Katz & Martin, ), therefore coauthorship is used in our research to assess the degree of collaboration. Coauthorship can be represented in terms of the numbers of individuals (Cunningham & Dillon, ), the numbers of institutions (Chua & Yang, ), and the numbers of countries of coauthors (Ordonez‐Matamoros et al., ). As discussed previously, collaboration between researchers has become a new research mode and has increased the number of coauthored publications.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as in many developing countries, it experiences a rapid process of institutionalization of the scientific and technological community thanks to policies that prioritize the creation of research groups as a legitimate organizational unit able to promote knowledge production with the support of public funding (Orozco et al, 2013). Second, also as most emerging economies, these teams have become increasingly international (Ordóñez‐Matamoros, Cozzens, & Garcia, 2010), mostly due to both private and public policies dedicated to that goal using a variety of tools and resources. Third, as most Science and Technology (S&T)‐developing countries, Colombia lacks appropriate amounts of scientists and engineers, infrastructure, investment, and institutional support.…”
Section: Institutionalization and Internationalization Of Colombian Smentioning
confidence: 99%
“…Regarding the internationalization process, despite the fact that Colombia lacks appropriate numbers of scientists and engineers, infrastructure, investment, and institutional support (Lemarchand, 2010; Vestergaard, 2005), with very low investment on R&D as a proportion of GDP (historically less than 0.3%), the international visibility of its research teams has increased steadily during the last decades, with IRC explaining a large portion of this phenomenon (Ordóñez‐Matamoros et al, 2010). According to Ordóñez et al (2010), as shown in Table 1, which contains the most updated data on the topic available, the proportion of articles published in collaboration with foreign partners grew constantly between 1980 and 2010. Since the 1990s the number of such articles published in high quality journals outnumbers those written without international collaboration, where, according to Fernández, Gómez, and Sebastián (1998), most of the collaborations take place with partners located in the United States and in Europe.…”
Section: Institutionalization and Internationalization Of Colombian Smentioning
confidence: 99%